1963
DOI: 10.1002/macp.1963.020660103
|View full text |Cite
|
Sign up to set email alerts
|

Über die polymerisation von acrylnitril mit silbernitrat

Abstract: ZUSAMMENFASSUNG:Die Polymerisation von Acrylnitril mit AgNO, in Substanz und in Losung wird untersucht. I n orientierenden kinetischen Versuchen wird gefunden, daB die Reaktion nach einem radikalischen Mechanismus ablauft ; sie wird durch Licht katalysiert. AuBerdem wird die Aktivitit einer Reihe anorganischer Salze und organischer Nitrate bei der Initiierung der Polymerisation gepriift. Die Reaktionsmoglichkeiten werden diskutiert. SUMMARY:The polymerization of acrylonitrile with AgNO, in bulk and in solution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1966
1966
1973
1973

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…cationic initiation (26) VCZ + AgCIO4 -H2CLCH4 cationic initiation (27) The former is the oxidation of the benzene anion radical to prevent recombination of the cation radical with the anion radical. The latter is the stabilization of the cation radical to facilitate cationic initiation.…”
Section: Vczmentioning
confidence: 99%
“…cationic initiation (26) VCZ + AgCIO4 -H2CLCH4 cationic initiation (27) The former is the oxidation of the benzene anion radical to prevent recombination of the cation radical with the anion radical. The latter is the stabilization of the cation radical to facilitate cationic initiation.…”
Section: Vczmentioning
confidence: 99%
“…Other lanthanides in the +3 valence state also serve as sensitizers for photopolymerization (155,297). Soluble silver salts are photoinitiators for polymerization of acrylonitrile using near-ultraviolet radiation (290). It has been suggested that the initiation involves the photoreduction of Ag+ (289).…”
Section: Inorganic Ionsmentioning
confidence: 99%